Comprehensive genomic and metabolomic analysis revealed the physiological characteristics and pickle like odor compounds metabolic pathways of Bacillus amyloliquefaciens ZZ7 isolated from fermented grains of Maotai-flavor baijiu - Yang, Liang; Zeng, Shuangran; Zhou, Meidi; Li, Yuetao; Jiang, Zeyuan; Cheng, Pingyan; Zhang, Chunlin (Frontiers in Microbiology, 2023)
Pickle like odor (PLO) is one of the main defective flavors of Maotai flavor baijiu (MFB). Understanding and controlling the PLO compounds producing strains not only solves the problem of PLO from the source, but also ensures the high-quality production of MFB. However, the relevant research on PLO compounds producing strains has not been reported in MFB. In this study, we identified a Bacillus amyloliquefaciens ZZ7 with high yield of PLO compounds in the fermented grains of MFB, and measured its physiological characteristics. It produces 627 volatile compounds and 1507 non-volatile compounds. There are 7 volatile sulfur compounds that cause the PLO, the content of dimethyl disulfide, dimethyl trisulfide, and dimethyl sulfur is relatively high, accounting for 89.43% of the total volatile sulfur compounds. The genome size of B. amyloliquefaciens ZZ7 is 3,902,720 bp with a GC content of 46.09%, and a total of 3948 protein coding genes were predicted. Moreover, the functional annotation of coding genes and an assessment of the metabolic pathways were performed by genome annotation, showing it has strong ability to transport and metabolize amino acids and carbohydrates. Comprehensive genomic and metabolomic analysis, the metabolic pathway of PLO compounds of B. aminoliquefaciens ZZ7 was revealed, which mainly involves 12 enzymes including sulfate adenylyltransferase, cysteine synthase, cystathionine γ-synthase, etc. This work provides biological information support at both genetic and metabolic levels for the mechanism of B. amyloliquefaciens ZZ7 to synthesize PLO compounds, and provides a direction for the subsequent genetic modification of ZZ7 to solve PLO from the source in the MFB.